ANALISIS HUKUM TERHADAP PENERBITAN SERTIFIKAT GANDA OLEH ATR/BPN KOTA GORONTALO BERDASARKAN PUTUSAN PENGADILAN TATA USAHA NEGARA GORONTALO (NOMOR:15/2023/PTUN.GTO) - Muhamad Isra Yunus; Hijrah Lahaling; Aliyas Aliyas (Unisan Law Review, 2026)
ABDUL ISRA MUHAMAD YUNUS. H1120124. LEGAL ANALYSIS OF THE ISSUANCE OF DUPLICATE CERTIFICATES BY THE GORONTALO CITY'S NATIONAL LAND AGENCY UNDER THE VERDICT OF THE GORONTALO STATE ADMINISTRATIVE COURT (NUMBER: 15/2023/PTUN.GTO.) The objectives of this research are (1) to find the factors causing the issuance of duplicate certificates by the National Land Agency of Gorontalo City, and (2) to determine how the National Land Agency of Gorontalo City resolves the issue of duplicate certificates. This research uses a normative legal research method, namely legal research that examines written law from the perspectives of theory, history, philosophy, comparison, structure and composition, scope and material, general explanations of each article, formality, and the binding force of a law, but does not cover its applied aspects or implementation. The issuance of land certificates is one of the government's efforts to provide legal certainty and protect land rights for the public. Duplicate certificates are a situation where two or more land title certificates are issued for the same or overlapping plots of land, ultimately leading to conflict between owners and legal uncertainty. This problem not only harms the public but also reflects weaknesses in Indonesia's land administration system. To better understand the causes, two key indicators that often trigger them can be analyzed: overlapping ownership and administrative errors. In addressing this issue, the National Land Agency of Gorontalo City plays a crucial role in resolving disputes, both through administrative and legal channels. As the technical agency responsible for land registration, it strives to resolve these disputes using an approach that prioritizes peaceful resolution, while still providing legal recourse if necessary. The National Land Agency of Gorontalo City resolves disputes over duplicate certificates through two primary mechanisms: mediation (non-litigation) and court proceedings (litigation). Keywords: duplicate certificates, National Land Agency, State Administrative Court decisions